Analysis of Student Perceptions of The Benefits of Entrepreneurship Education To Grow Student Entrepreneurial Intentions - Novanda, Ridha Rizki (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2022)
Purpose – This to analyze students' perceptions of entrepreneurial intentions Methodology/approach – The research was conducted on Indonesian students who had already received entrepreneurship courses. The selection of respondent groups was carried out purposively and data were collected through questionnaires distributed through online surveys. The number of respondents involved in this study were 300 respondents. Data analysis used descriptive quantitative for the analysis of respondents' perceptions. Findings – Based on the results of the analysis, it was found that students' perceptions of entrepreneurial intentions were in the middle category in all aspects. Starting a new business by identifying opportunities, Creating something different by identifying opportunities, Develop business by evaluating existing opportunities, Develop skills by evaluating opportunities, and Operating a new business are in the medium category. This shows that the entrepreneurial intention of students from entrepreneurship education is not yet high. There are still students' doubts about running a business. Novelty/value – Entrepreneurial intentions for students at various universities in Indonesia